Specific anti-glycan antibodies are sustained during and after parasite clearance in Schistosoma japonicum-infected rhesus macaques. - Y Y Michelle Yang; Xiao Hong Li; Katarzyna Brzezicka; Niels-Christian Reichardt; R Alan Wilson; Angela van Diepen; Cornelis H Hokke (Public Library of Science (PLoS), 2017)
BACKGROUND:Human immunity to Schistosoma infection requires many years of exposure, and multiple infections and treatments to develop. Unlike humans, rhesus macaques clear an established schistosome infection naturally at the same time acquiring immunity towards re-infection. In macaques, schistosome egg production decreases after 8 weeks post-infection and by week 22, physiological impairment of the worm caused by unclarified antibody-mediated processes is observed. Since strong antibody responses have been observed against schistosome glycan antigens in human and animal infections, we here investigate if anti-glycan antibodies are associated with immunity against schistosome infections in macaques. METHODS:We used a microarray containing a large repertoire of glycoprotein- and glycolipid-derived glycans from different schistosome life stages to analyse anti-glycan serum IgG and IgM from S. japonicum-infected macaques during the course of infection and self-cure. We also used an in vitro schistosomula assay to investigate whether macaque sera containing anti-glycan antibodies can kill schistosomula. CONCLUSIONS/SIGNIFICANCE:Antibody responses towards schistosome glycans at week 4 post-infection were dominated by IgM while IgG was high at week 8. The profound increase in IgG was observed mainly for antibodies towards a large subset of glycans that contain (multi-)fucosylated terminal GalNAcβ1-4GlcNAc (LDN), and Galβ1-4(Fucα1-3)GlcNAc (LeX) motifs. In general, glycans with a higher degree of fucosylation gave rise to stronger antibody responses than non-fucosylated glycans. Interestingly, even though many IgG and IgM responses had declined by week 22 post-infection, IgG towards O-glycans with highly fucosylated LDN motifs remained. When incubating macaque serum with schistosomula in vitro, schistosomula death was positively correlated with the duration of infection of macaques; macaque serum taken 22 weeks post-infection caused most schistosomula to die, suggesting the presence of potentially protective antibodies. We hypothesize that IgGs against highly fucosylated LDN motifs that remain when the worms deteriorate are associated with infection clearance and the resistance to re-infection in macaques.